Sociocultural–psychological predictors influencing parents' decision-making regarding HPV vaccination for their adolescent daughters in mainland China: An extended TPB model - Zhang, Lingmin; Yang, Jian; Cao, Ye; Kang, Wanying (Frontiers in Public Health, 2023)
Enhancing human papillomavirus (HPV) vaccine uptake rates to protect women’s health is an important public health issue worldwide. China has taken a series of measures in recent years to promote HPV vaccination among school-aged girls, but the vaccine uptake rate remains low. Parents are the decision-makers regarding vaccination for young girls, therefore investigating the factors influencing parents’ vaccination-related decision-making is key to solving the problem. However, research on these factors in mainland China is insufficient. This study aimed to establish a newly extended theory of planned behavior model incorporating the additional variables of exposure to HPV-related stories (positive/negative), perceived risk, affective reactions (pride/regret), injunctive norms on the Internet and perceived moral obligation to examine the sociocultural–psychological predictors of parents’ HPV vaccination-related decision-making for girls aged 13–15 years in mainland China. A cross-sectional online survey using quota sampling was conducted in February 2022. Four hundred and five valid and qualified questionnaires were obtained. Partial least squares structural equation modeling was performed by SmartPLS 3 (i) to evaluate the reliability and validity of the measurement models of 11 constructs, and (ii) to test the effect relationships of the sociocultural–psychological predictors on parents’ intention to vaccinate their daughters. The study findings showed that parental decision-making regarding HPV vaccination was influenced by sociocultural and psychological factors. At the level of individual psychological factors, exposure to positive stories was significantly associated with perceived vaccine effectiveness, which strongly predicted the attitude toward vaccination; anticipated pride had more positive influence on vaccination-related decision-making than anticipated regret. In terms of social influence, injunctive norms on the Internet had a significantly positive influence on vaccination intention, similar to descriptive norms. Perceived moral obligation at the cultural level was the strongest predictor of parental decision-making regarding HPV vaccination. The study suggested that HPV vaccination communication campaigns for parents should pay attention to the influence of social group on the Internet, deliver the positive affective reaction of anticipated pride by highlighting “It’s parental moral obligation to vaccinate daughters” in the contents, and actively disseminate the positive HPV vaccination-related stories to influence attitude toward HPV vaccination positively.